A história das invenções contada por Monteiro Lobato: um olhar sobre o progresso, trabalho e tecnologia - Tszesnioski, Roberta Reis Bahia (2014)
The present dissertation aims to analyze the representations of the worker,work, technology and progress in child labor ―História das Invenções‖, of Monteiro Lobato, published in 1935. It is considered that the representations of technology, progress and work, present in the work, demonstrate the process of recontextualization, directed by Monteiro Lobato, by adapting the work of Hendrik van Loon, to the Brazilian context, which is marked by new political, economic and ideological tensions. To this end, it is necessary to verify that the perspective of progress is included in the work, since, for the Brazilian writer, progress is associated with some types of inventions, which impacted the world of work. Two progress concepts are presented in the narrative: at first the evolutionary process by which the human being passed, idea strongly related to evolutionary theories. In a second moment, the author shows the progress as a tool of modernization, being closely related to inventions. The inventions considered as a technological apparatus, are extensions of human bodies. Also discusses the approach of Monteiro Lobato on the use of the machinery and its relationship with the employee. It will be seen that, for the Brazilian writer, the machine came to make work efficient and complete man, being a fundamental instrument of human progress and a mechanism of rationalization and improvement of the worker. We will seek to demonstrate that the idea of progress in Lobato is associated with the mechanization of the work, which would bring modernization to the social and economic structure of the country.